Simultaneous editing of GABA and GSH with Hadamard-encoded MR spectroscopic imaging - Chan, Kimberly L. (Magn Reson Med, 2019)
PURPOSE: To evaluate the feasibility of simultaneous MR spectroscopic imaging (MRSI) of gamma-aminobutyric acid (GABA) and glutathione (GSH) in the human brain using Hadamard Encoding and Reconstruction of MEGA-Edited Spectroscopy (HERMES). METHODS: PRESS-localized MRSI was performed in GABA and GSH phantoms and in the human brain (n=3) using HERMES-editing and compared to conventional MEGA-editing of each metabolite. Multiplet patterns, signal intensities, and metabolite crosstalk were compared between methods. GABA+ and GSH levels were compared between methods for bias and variability. Linear regression of HERMES-MRSI GABA+/H(2)O and GSH/H(2)O versus gray matter fraction were performed to assess differences between gray matter (GM) and white matter (WM). RESULTS: Phantom HERMES-MRSI scans gave comparable GABA+ and GSH signals to MEGA-MRSI across the PRESS-localized volume. In vivo, HERMES-reconstructed GABA+ and GSH values had minimal measurement bias and variability relative to MEGA-MRSI. Inter-subject coefficients of variation (CV) from two regions within the PRESS-localized volume for HERMES and MEGA were ~6–12% for GABA+ and 6–19% for GSH. Inter-region CVs were 5 – 15% for GABA+ and 3 – 17% for GSH. GABA+/H(2)O and GSH/H(2)O ratios were ~1.8 times higher and ~1.9 times higher respectively in GM than in WM. CONCLUSION: HERMES-MRSI of GABA+ and GSH was found to be practical in the human brain with minimal measurement bias and comparable variability to separate MEGA-edited acquisitions of each metabolite performed in double the scan time. HERMES-MRSI is a promising method for simultaneously mapping the distribution of multiple low concentration metabolites.